Competition and Entry in Banking: Implications for Stability and Capital Regulation - Arnoud W.A. Boot; Matej Marinc (Tinbergen Institute, 2006)
We assess the influence of competition and capital regulation on the stability of the banking system. We particularly ask two questions: i) how does capital regulation affect (endogenous) entry; and ii) how do (exogenous) changes in the competitive environment affect bank monitoring choices and the effectiveness of capital regulation? Our approach deviates from the extant literature in that it recognizes the fixed costs associated with banks' monitoring technologies. These costs make market share and scale important for the banks' cost structures. Our most striking result is that increasing (costly) capital requirements can lead to more entry into banking, essentially by reducing the competitive strength of lower quality banks. We also show that competition improves the monitoring incentives of better quality banks and deteriorates the incentives of lower quality banks; and that precisely for those lower quality banks competition typically compromises the effectiveness of capital requirements. We generalize the analysis along a few dimensions, including an analysis of the effects of asymmetric competition, e.g. one country that opens up its banking system for competitors but not vice versa.
Keywords: G21; L13; L50; 330; Banking; Capital regulation; Competition; Bank; Regulierung; Markteintritt; Bankenaufsicht; Wettbewerb; Mathematische Ökonomie